Implications of global carbon governance for corporate carbon emissions reduction - Wang, Yunjing; Yao, Guiying; Zuo, Ying; Wu, Qichun (Frontiers in Environmental Science, 2023)
Global warming not only affects biodiversity, but also threatens human health and wellbeing. As the main source of greenhouse gas emissions, enterprises play a critical role in carbon emissions reduction. However, only a small number of enterprises have disclosed their “low-carbon transition roadmap”, primarily due to the lack of immediate payoffs of green investment, which is disadvantageous to achieve net-zero emissions. First, through case analysis of carbon governance in typical countries around the world, we identify effective emissions reduction measures that firms can learn from. Next, this paper summarizes the multi-dimensional impact framework of corporate carbon emissions reduction. Last, we propose a carbon emissions reduction roadmap for companies from four aspects: companies should 1) actively engage in the carbon emissions trading system, 2) increase the application of green technology, 3) enhance corporate governance structure, and 4) ensure sufficient cash flow for low-carbon transition. This study contributes to the framework of corporate sustainable transition, providing practical references for balancing corporate environmental footprint and value growth.